Trends in the Development of Game-Based Science Learning Research in Elementary Schools - Lestari, Rizky; Rohmani (Universitas Pendidikan Ganesha, 2025)
Over the past 15 years, research on game-based science learning in elementary schools has fluctuated with uneven publication distribution. To address this, stronger international collaboration, utilization of the latest technology, and the use of appropriate keywords are needed. This study aims to identify and visualize publications related to game-based science learning in elementary schools during the period 2008-2023, using descriptive bibliometric methods. From the analysis of 53 articles taken from the Scopus database, it was found that Taiwan and the United States were the main contributors, with significant international collaboration. This study used a qualitative approach with bibliometric and content analysis methods. Data were collected through documentation studies. The data analysis methods used were thematic analysis for content and quantitative descriptive analysis for publication trends. The main results of the study indicate a significant increasing trend in the use of game-based science learning in elementary schools, with the dominant use of digital game media and educational board games integrated with active learning approaches such as PBL and STEM. The study also found that the primary focus of development is directed at improving critical thinking skills, collaborative learning, and mastery of basic science concepts. It is concluded that game-based science learning is becoming an increasingly relevant and effective strategy in supporting student engagement and improving learning outcomes.